Kinematic differences in a skating stop-and-go task between male and female ice hockey players - Robbins, S. M.; Hallihan, A.; Renaud, P. J.; Valevicius, A.; Holman, L.; McPhee, B.; Pearsall, D. J. (International Journal of Performance Analysis in Sport, 2025)
Kinematic differences exist between sexes when skating, but other tasks have not been compared. The objective was to compare the centre of mass (COM) and joint angles between female and male ice hockey players during a Stop-and-Go task. Male (n = 8) and female (n = 9) players completed a Stop-and-Go requiring them to skate (PRE phase), complete a side parallel stop (STOP phase), and then skate back to the initial position (POST phase). Kinematic data were collected with an 18-camera motion capture system. Spatiotemporal variables, COM, and joint angles were calculated. T-tests compared spatiotemporal variables between sexes, while 2-way analysis of variance compared COM and joint angle discrete values between sexes and phases. Males completed Stop-and-Go faster than females (mean difference = 0.36 s, p = 0.035). Females had higher COM vertical positions (p = 0.023) and lower velocities in the forward direction (p < 0.001). During PRE phase at the inside hip, females had greater adduction (p = 0.006), less extension (p = 0.027), and less flexion range of motion (p = 0.027). Males had greater bilateral knee flexion (p = 0.029) across the phases. Joint angle and COM differences might account for the faster completion times in males. Increasing joint flexion maybe a strategy to improve performance during changes in direction in ice hockey players.